Age-dependent cardiac remodelling – role of sex hormones. (25th November 2020) - Haider, A; Bengs, S; Warnock, G; Akhmedov, A; Kozerke, S; Kwiatkowski, G; Mueller Herde, A; Kraemer, S.D; Weber, B; Schibli, R; Mu, L; Kaufmann, P.A; et al.
Abstract: Background: While cardiovascular mortality in women has exceeded those in men, women continue to be underrepresented in cardiovascular clinical trials. Further, preclinical experiments are predominantly conducted in male animals, rendering sex-specific variables contributing to cardiovascular disease largely unknown. As age and menopause remain to be key risk factors for cardiovascular disease in women, the aim of this study was to identify key variables of cardiac remodelling in the aging female and male heart, as well as to assess effects of sex hormone deprivation on left ventricular (LV) morphology, LV function and cardiac sympathetic activity. Materials and methods: Gonadectomized and sham-operated FVB/N mice of both sexes were subjected to positron emission tomography (PET) and cardiac magnetic resonance (CMR) imaging at the age of 4 (young cohort) and 20 (aged cohort) months (total n=123, 55% females). Following tail-vein injection of [11C]meta-hydroxynorephedrine ([11C]mHED), a widely used PET probe in preclinical and clinical assessment of cardiac sympathetic integrity, animals were scanned and cardiac sympathetic outflow was derived from myocardial [11C]mHED uptake. Cardiac parameters including LV volumes and left ventricular ejection fraction (LVEF) were obtained from electrocardiogram (ECG)-gated CMR imaging. Results and discussion: A significant increase of LVEF was observed in aging females (p=0.012, Figure 1), but not in males. The latter was not associated with a higher cardiac output, and was a consequence of reduced LV end-systolic volumes (p=0.008), unveiling a substantial reduction of size in the aging female heart. As this age-dependent observation was not present in gonadectomized animals (p=0.414), the lack of growth-stimulating estrogen might account for reduction of cardiac size in aging females. Thus, despite a significantly heightened body weight, female heart size is reduced with age. Accordingly, sufficient cardiac output was maintained via increased heart rate (p=0.005) and cardiac sympathetic activity (p=0.040, Figure 1). Gonadectomy accelerated age-dependent changes in LV morphology and function in female mice. While sex hormone deprivation blunted cardiac sympathetic activity and norepinephrine levels in male mice, an opposite trend was observed in females. Conclusion: Despite increasing body weight with age, aged female and male hearts maintain a stable circulatory blood supply, however, by distinct mechanisms. While the "shrinking" female heart requires an increased heart rate and cardiac sympathetic activity to compensate for smaller ventricular volumes, aging males maintain cardiac size. Importantly, sex hormone deprivation at a young age accelerates age-dependent changes in LV morphology and function in female mice, but not in male mice. The increased sympathetic activity reflects a higher stress level in aged females that might expose them to a higher cardiac vulnerability at postmenopausal age. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation; Swissheart Foundation